師資生教師信念之縱貫性研究：以任教意願為調節變項 Teaching Willingness as a Moderator: A Longitudinal Study on Preservice Teachers' Teacher Belief - 蕭佳純 Chia-Chun Hsiao (National Taiwan Normal University, 2020)
在師資的養成教育過程中，對於教師信念的發展極為重要，因此，採用縱貫性研究的角度瞭解師資生的教師信念變化有其必要性。本研究以 232 位師資生為對象，分析教師信念的成長趨勢，以及實習時的任教意願對於教師信念的初始狀態和成長趨勢的影響。本研究在 1年半期間一共進行三次調查，利用階層線性模式的統計技術，分析結果顯示：一、師資生教師信念一共有學生的管教、課程教學計畫、教學評量及學生的學習四個構面，以四個構面來看，都是呈現一線性向下的成長趨勢圖形；二、任教意願對教師信念的初始狀態具有影響； 三、任教意願對於課程教學計畫、教學評量的成長趨勢有負向調節的影響，也就是說，任教意願愈高的師資生，其課程教學計畫、教學評量的下降趨勢會較緩。依據上述分析結果，本研究提出相關建議及未來研究的建議。 With 232 preservice teachers as research subjects, the present study analyzed the growth trend of teacher belief and the effect of teaching willingness on the initial state and growth trend of teacher belief during practical training. The research survey was conducted three times in one and a half years. An analysis of the hierarchical statistics revealed the following: (1) Preservice teachers' teacher belief comprises four dimensions, namely student discipline, curriculum and teaching planning, teaching and evaluation, and student learning, all of which present a linear downward growth trend. (2) Teaching willingness exerts effects on the initial state of teacher belief. (3) Teaching willingness appears to negatively moderate the growth trend of curriculum and teaching planning and teaching and evaluation. In other words, preservice teachers with higher teaching willingness exhibit a slow declining trend of curriculum and teaching planning and teaching and evaluation. According to the analysis results, the paper propose relevant suggestions for education institutes/teaching practitioners and suggestions for future research.